Reparations in the Caribbean and Diaspora - Prilly Bicknell-Hersco (Caribbean Studies Students' Union, 2020)
Millions of people have been victim to violent and inhumane social injustices, many of them based on racial and cultural hierarchies. The Nazi Holocaust or the colonization of North America through the genocide of indigenous populations are examples of such instances. When these victims have no direct claim on those who committed the harm, the victims turn to the government for reparations. It can be said that the enslavement of Africans in the Caribbean is another painful and violent injustice, yet few reparations, if any at all, have been paid out to those most affected by the transatlantic slave trade. In 2013, CARICOM released an official request for Reparations for the Native Genocide and Slavery from the United Kingdom and the other European colonies. The discussion of reparations for slavery has ignited debate worldwide.